Design of a low-cost IoT-based biofloc water quality monitoring system - Bakhit, Abdelmoneim Ahmed; Mohd Faizal, Jamlos; Muhammad Aqil Hafizzan, Nordin; Mohd Aminudin, Jamlos; Rizalman, Mamat; M. A. M., Nawi; Agus, Nugroho (Semarak Ilmu Publishing, 2024)
This paper proposes an IoT-based BFT water monitoring system that can measure water parameters such as pH, DO, TDS, and EC. The collected data is displayed remotely via the BLYNK cloud and Node-RED via an MQTT broker. Moreover, a mobile application monitors all water parameters in real-time, notifying users when a parameter exceeds the ideal value. This study suggests that the proposed system based on IoT is an excellent option for a cost-effective BFT system.